Effectiveness of the E-UKGS Web System in Improving School Dental Health Management and Teachers’ Roles - Dyah Saffana Arsinta; Supriyana Supriyana; Lanny Sunarjo (Center of Excellent (Pusat Unggulan Iptek), 2026)
Maintaining oral health is a critical component of overall health, particularly among school-aged children who are prone to dental caries and gingivitis. In Semarang, the School-Based Dental Health Program (UKGS) faces challenges such as manual record-keeping, limited monitoring, and insufficient teacher involvement, which hinder program effectiveness. This study aimed to develop and evaluate E-UKGS, a web-based system designed to support teachers and dental health professionals in planning, implementing, monitoring, and evaluating UKGS activities effectively. This study employed a Research and Development (R&D) approach using the ADDIE framework, combined with a pre-experimental one-group pretest–posttest design to assess effectiveness, encompassing five stages: analysis, design, development, implementation, and evaluation. Needs assessment involved interviews and observations with the Health Office, dental professionals, and teachers, complemented by literature review. Expert validation was conducted with UKGS specialists, IT professionals, dental staff, and elementary school teachers. Implementation involved small- and large-scale trials including teachers, students, parents, and health personnel. Participants included 5 dental health professionals, 5 teachers, 56 students, and 22 parents in the implementation phase. All the samples selected using purposive sampling. Data were collected using observation checklists, feasibility questionnaires based on ISO 9126, and pretest–posttest instruments. Data analysis was conducted using descriptive statistics, Paired T-Test, Wilcoxon, and Interclass Correlation Coefficient (ICC). The results showed that E-UKGS significantly improved UKGS management, including planning, implementation, monitoring, evaluation, and accessibility (p < 0.05). Teachers’ roles in promotive and preventive activities also improved significantly (p = 0.04). Feasibility testing indicated that the system was highly suitable for independent use, with average scores of 97.3% for dental health professionals and 96% for teachers (p = 0.000). In conclusion, E-UKGS is an effective and feasible web-based system that enhances program management and strengthens teachers’ roles in school dental health efforts. This platform has the potential to improve the quality and sustainability of UKGS implementation in elementary schools.